2023
DOI: 10.1371/journal.pone.0284817
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial and fungal community composition and community-level physiological profiles in forest soils

Abstract: We characterized the potential functioning and composition of the bacterial and fungal communities in the O and A horizons of forest soils using community-level physiological profile (CLPP) based on BIOLOG analysis, and polymerase chain reaction–denaturing gradient gel electrophoresis (PCR-DGGE) analysis of 16S and 18S rDNA fragments, respectively. In addition, relationships between the potential functioning and the community composition in each horizon, and between the O and A horizons, were assessed using Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
(42 reference statements)
0
0
0
Order By: Relevance
“…The DGGE technique is based on the differences in the sequence-dependent melting behavior of double stranded DNA (Shekhar et al, 2020). Different studies have reported the effective use of the DGGE technique for monitoring microbial communities in heavy metal and petroleum hydrocarbon remediation processes (Kunito et al, 2023;Das & Panda, 2022). Currently, there are methods such as Next Generation Sequencing (NGS), based on 16S ribosomal sequencing that allows greater resolution and sensitivity for the quantification of operational taxonomic units (OTUs), including those underrepresented in the environmental sample analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…The DGGE technique is based on the differences in the sequence-dependent melting behavior of double stranded DNA (Shekhar et al, 2020). Different studies have reported the effective use of the DGGE technique for monitoring microbial communities in heavy metal and petroleum hydrocarbon remediation processes (Kunito et al, 2023;Das & Panda, 2022). Currently, there are methods such as Next Generation Sequencing (NGS), based on 16S ribosomal sequencing that allows greater resolution and sensitivity for the quantification of operational taxonomic units (OTUs), including those underrepresented in the environmental sample analyzed.…”
Section: Introductionmentioning
confidence: 99%